The Impact of Smartphone Addiction on Personality and Fine and Rude Motor Development in Elementary Children - Yhesa Rooselia Listiana; Triana Lestari (Universitas Muhammadiyah Enrekang, 2021)
Nowadays, almost everyone has a smartphone. This smartphone is a smart phone which contains a variety of advanced features whose function is to simplify human life. Because this smartphone works easily, everyone can be worn. Therefore, not a few children already have smartphones. Smartphones actually have a lot of impact, both positive and negative. Smartphones can affect personality and can prevent children from accomplishing the developmental tasks they have to go through.